Scheming of mechanical properties of molybdic acid added sisal glass fiber reinforced epoxy composite. (2021) - N., Rajesh Jesudoss Hynes; G., Manoj Kumar; C., Uthranarayan
Abstract: The widespread use of sisal fiber and glass fiber-based composites has spawned a slew of novel applications in research and innovation. The goal of this project is to evaluate the mechanical characteristics of hybrid glass fiber-sisal reinforced epoxy with molybdic acids, such as tensile and hardness. Because of their biodegradability, increased qualities in more particular strength, and low weight, these materials-based composites are more intriguing. Using a scanning electron microscope (SEM), the internal morphology of the composite and shattered details of structures are analyzed in order to study the surface aspects of materials. Variations in fiber and matrix content are used to test the qualities of the hybrid composite material. When the samples were further configured, the results indicated that 40 percent Fiber with 60 percent Matrix demonstrated excellent qualities. It is now possible to meet the structural endurance requirements of automotive inside, outside parts, suitcases, helmets, and lampshades using the solutions obtained.